(untitled) (Biological Sciences - PJSIR, 2009)
On application of the seed oil of ripe and unripe fruits of Citrus sinensis, C. paradisi and C. aurantifolia to the cowpea bruchid, Callosobruchus maculatus (F) for three days, a dose of 0.5 ml of C. sinensis gave, significantly, high mortality rate upto 85%. In case of C. aurantifolia, mortality ranged from 75% to 100%. Same least dosage of seed oil of ripe C. paradissi produced 58.8% to 100% mortality, whereas, except the dose of 0.5 ml, all the other treatments of unripe C. paradissi resulted in 100% mortality after 24 h.